2012
DOI: 10.1089/bio.2012.0016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Pre-analytical Variables on VEGF Gene Expression and Circulating Protein Concentrations

Abstract: The most reliable conditions for measuring both circulating VEGF and its gene expression are to reduce time between blood collection and centrifugation, and to avoid multiple freeze-thaw cycles. Serum collection tubes with no additive and no separator were less sensitive to the pre-analytical variations analyzed in this study. Freezing delay had a significant influence on VEGF protein expression in tissue samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 41 publications
(43 reference statements)
0
30
1
Order By: Relevance
“…The individual data records are pseudoanonymized according to the European (GDPR directive) and French (CNIL) laws in order to protect the participants' privacy. Sample quality controls are regularly performed following a biospecimen research schedule [8,18,23].…”
Section: Sample Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The individual data records are pseudoanonymized according to the European (GDPR directive) and French (CNIL) laws in order to protect the participants' privacy. Sample quality controls are regularly performed following a biospecimen research schedule [8,18,23].…”
Section: Sample Managementmentioning
confidence: 99%
“…The Diagmicoll main cohort (Clinical trials reference: NTC03912246) affords bio-resources from healthy subjects primarily, for the National Reference Centers, so as to optimize and develop new diagnostic methods [1,3,4,5,8,10,13,20,21,28]. The CoSImmGEn cohort (Clinical trials reference: NTC03925272) has been set up to take in charge more complex needs such as longitudinal studies of the immune system and other integrative (e.g.…”
mentioning
confidence: 99%
“…In terms of protein preservation, there is variability for individual proteins. In muscle biopsies, vascular endothelial growth factor protein expression tended to be higher in specimens subjected to a 30 or 60 minutes cold ischemia time compared to those frozen within 15 minutes of tissue removal [38]. Significant reduction in immunohistochemistry (IHC) staining for progesterone receptor in breast cancer samples occurs after 2 hours for non-refrigerated samples [39].…”
Section: Considerations In the Procurement Of Tissue And Blood Biomentioning
confidence: 99%
“…Baumann et al reported that the best reproducibility of proteomic patterns is with a single thawing of frozen serum samples and that repeated freeze-thaw cycles lead to significant changes of serum and plasma proteomes [72]. Vascular endothelial growth factor (VEGF) levels in plasma significantly changed with the number of freeze-thaw cycles [38, 73]. Hsieh and colleagues demonstrated that repeated freezing at −80°C and thawing on ice for up to ten times did not present any obvious changes in low-molecular-weight serum and plasma proteomes [45].…”
Section: Freeze-thaw Cycles and Their Effect On Biospecimen Qualitymentioning
confidence: 99%
See 1 more Smart Citation